A regional experiment to test green manure cover crops and evaluate the role of Internet based networking - Tarawali, G.; Markham, R.; Carsky, R.J.; Keatinge, J.D.H. (2000)
Land degradation in the West African subregion is threatening the food security and livelihoods of both rural and urban populations. Green manure cover crops have the potential of reversing such trends. A wide range of stakeholders have been involved in the promotion of these technologies and it became apparent that a network was needed to provide a common forum where these cover crop enthusiasts could discuss their problems and identify opportunities for synergy. With the advancement of ICT (Information Communication Technology) it was also conceived that the use of Internet-based technologies would enhance such a sustainable research and development programme. It was against the background that CCROPNET (Cover Crops Network) were provided by USAID. As part of this exercise, researchers are testing the contribution of two cover crop species to sustainable agriculture and simultaneously evaluating the effectiveness of the internet in conducting such a trial. Results so far have shown that ICT has potential in promoting the quality of research in the region, but some constraints have arisen, including technical and financial problems with connectivity and unfamiliarity with the use of e-mail software, etc. Continued efforts to alleviate these constraints and encourage exchange of information, especially amongst peers, are recommended.